Navajo materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Fincher, Beverly Hung, 1933-; Tschopik, Harry, 1915-1956; Kinkade, M. Dale (Marvin Dale), 1933- (1938)
Five items relating to Navajo language and culture have been identified in the C. F. Voegelin Papers. They are all in Subcollection II. There is relevant correspondence with M. Dale Kinkade (regarding a comparative work on color and anatomical terms in Salish, Navajo, and English); Navajo material in a folder labeled "Athabascan (Chipewyan)" as well as a separate Navajo folder in Series II. Research Notes, Subseries II. Na-Dene; a Navajo story ("Coyote files with the Birds") in the Southwestern Indian Tales category in Series III. Works by Voegelin, Subseries II: American Indian Tales for Children; Harry Tschopik's map of "Indian Languages in New Mexico, A.D. 1600" (1938) in Series III. Works by Voegelin, Subseries V: American Indian Languages; and Beverly Hung Fincher's article "On the Phonemic Status of Navaho Stress" (1959) in Series IV. Works by Others. Note that a digital image of Tschopik's map is available through the APS's Digital Library.